Mainstreaming Religious Moderation in Polytechnic, Quo Vadis? - Suhendar, Waway Qodratulloh; Assidiki, Hasbi; Hafidhuddin, Hafidhuddin; Hadikusuma, Riza; Rahman, Rini (Universitas Pendidikan Indonesia, 2022)
Abstract This article tries to dissect the direction of the development and application of religious moderation values in the Polytechnic. Conceptually, religious moderation is a process of believing in, understanding and practicing balanced religious teachings in the life of the nation and state. This research is a qualitative research, in which data from field studies were collected through interviews, observation, and documentation studies. Field research was carried out at the Bandung Polytechnic (Polban) and the Jakarta State Polytechnic (PNJ). The results of the study show that the direction of developing religious moderation in the Polytechnic prioritizes the cultivation of the value of tolerance which is entrusted to all Religious Education courses. The inculcation of the value of religious moderation is carried out through the delivery of material about tolerance in the views of religions in Indonesia and the implementation of joint activities in the form of inter-religious harmony projects. Abstrak Artikel ini mencoba membedah arah pengembangan dan penerapan nilai-nilai moderasi beragama di Politeknik. Moderasi Beragama secara konsep merupakan sebuah proses meyakini, memahami dan mengamalkan ajaran agama yang berimbang dalam kehidupan berbangsa dan bernegara. Penelitian ini adalah penelitian kualitatif, di mana data hasil studi lapangan dikumpulkan melalui wawancara, observasi, dan studi dokumentasi. Penelitian lapangan dilaksanakan di Politeknik Bandung (Polban) dan Politeknik Negeri Jakarta (PNJ). Hasil kajian menunjukkan bahwa arah pengembangan moderasi beragama di Politeknik mengedepankan pada penanaman nilai toleransi yang dititipkan pada semua mata kuliah Pendidikan Agama. Penanaman nilai moderasi beragama ini dilakukan melalui penyampaian materi tentang toleransi dalam pandangan agama-agama di Indonesia dan pelaksanaan kegiatan bersama dalam bentuk projek kerukunan antar umat beragama.